Distributive and Procedural Justice and Political Trust in Europe - Schnaudt, Christian; Hahn, Caroline; Heppner, Elias (Frontiers in Political Science, 2021)
Previous research underlines that a political system’s adherence to principles of distributive and procedural justice stimulates citizens’ political trust. Yet most of what is known about the relationship between justice and political trust is derived from macro-level indicators of distributive and procedural justice, merely presuming that citizens connect a political system’s adherence to justice principles to their trust in political authorities and institutions. Accordingly, we still lack a clear understanding of whether and how individual perceptions and evaluations of distributive and procedural justice influence citizens’ political trust, and how their impact might be conditioned by a political system’s overall adherence to principles of justice. In addition, previous research has implicitly assumed that the link between justice principles and political trust operates identically for all major political authorities and institutions, disregarding the possibility that citizens evaluate representative and regulative authorities and institutions on the basis of different justice criteria. Against this background, the aim of the present study is to (1) investigate the impact of individual evaluations of distributive and procedural justice on citizens’ political trust, (2) to analyze to what extent the effects of justice evaluations on political trust depend on political systems’ overall adherence to principles of distributive and procedural justice, and (3) to assess whether and in which ways the influence of justice evaluations differs for trust in representative and regulative authorities and institutions. Our empirical analysis covering more than 30,000 respondents from 27 European countries based on data from the European Social Survey (ESS) and the Varieties of Democracy (V-Dem) project demonstrates that (1) more positive evaluations of distributive and procedural justice foster citizens’ political trust, that (2) the impact of justice evaluations on political trust is amplified in political systems in which the overall adherence to justice principles is compromised, and that (3) different facets of distributive and procedural justice evaluations exert varying effects on citizens’ trust in representative as compared to regulative authorities and institutions. These findings entail important implications with regard to the relation between justice and political trust and the general viability of modern democratic systems.